Utilizing Polyethylene Terephthalate (PET) In Insulation Fired Clay Bricks (International Journal of Scientific Research and Management (IJSRM), 2024)
In order to improve the thermal insulation properties of fired clay bricks, the addition of polystyrene has been a common practice. However, in this study, we propose an alternative approach by substituting polystyrene with recycled polyethylene terephthalate (PET) derived from drinking water bottles. The PET is shredded and added to the brick composition, with a maximum inclusion level of 25%. Various tests were conducted to evaluate water absorption, apparent porosity, bulk density, cold crushing strength, and thermal conductivity of the bricks at temperatures up to 800 degrees Celsius. The results indicate that incorporating 20% crushed plastic by weight yields bricks comparable to ASTM C155-97 standard bricks.